Implementasi Program Building Learning Power (BLP) dalam Membentuk Karakter Disiplin Siswa SMP Cahaya Quran Islamic Boarding School (IBS) - Putri Ashfahani; Zuli Dwi Rahmawati (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
Character education is a crucial aspect in shaping students to be responsible, honest, and disciplined individuals. Discipline is highly necessary to build a generation that is obedient to rules, capable of managing time, and consistent in daily behavior. To achieve this goal, SMP Cahaya Quran Islamic Boarding School (IBS) implements the Building Learning Power (BLP) program. BLP is an educational approach developed by Guy Claxton that focuses on five components for building learning capacity: Resilience, Resourcefulness, Reflectiveness, Reciprocity, and Devoutness. The purpose of this research is to determine the implementation of the BLP program at SMP Cahaya Quran IBS and how the program shapes students' discipline character. This study uses a qualitative descriptive method with a field study approach. Data collection techniques were carried out through observation, interviews, and documentation. The research results show that the BLP program is implemented systematically through daily activities such as filling out journals, activity checklists, and inspirational storytelling sessions. This program has a positive impact on the formation of student discipline, both in terms of personal responsibility, learning regularity, and compliance with school rules. The supporting factors for the implementation of BLP include teacher involvement, school management support, and student enthusiasm. Meanwhile, the obstacles faced are in the form of limited implementation time and the uneven initial understanding of the BLP concept among students. Thus, the BLP program is proven effective in shaping students' discipline character in a boarding school educational environment.